2021
DOI: 10.1115/1.4049248
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Onshore and Offshore Environmental Parameters on the Leading Edge Erosion of Wind Turbine Blades: A Comparative Study

Abstract: The presence of rain-induced leading edge erosion of wind turbine blades (WTBs) necessitates the development of erosion models. One of the essential parameters for erosion modeling is the relative impact velocity between rain droplets and the rotating blade. Based on this parameter, the erosion damage rate of a WTB is calculated to estimate the expected leading edge lifetime. The environmental conditions that govern this parameter have site-specific variations, and thus, rain and wind loading on a turbine diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Note that this assumption may underestimate the lifetime calculated for the wind turbines installed at the coastal sites as shown in Verma et al 14 and Shankar Verma et al, 36 but it shouldn't affect the main findings and conclusions of the paper. Figure 5 presents the probability density function (PDF) of droplet size for different rain intensities ( I=0.1, 1, 10, 25 mm/h) using Best's DSD.…”
Section: Methodology and Case Studymentioning
confidence: 93%
“…Note that this assumption may underestimate the lifetime calculated for the wind turbines installed at the coastal sites as shown in Verma et al 14 and Shankar Verma et al, 36 but it shouldn't affect the main findings and conclusions of the paper. Figure 5 presents the probability density function (PDF) of droplet size for different rain intensities ( I=0.1, 1, 10, 25 mm/h) using Best's DSD.…”
Section: Methodology and Case Studymentioning
confidence: 93%
“…The droplet impact causes local pitting, progressive material loss and increases the local surface roughness of the leading edge, consequentially decreasing the overall aerodynamic efficiency [83][84][85][86][87]. The damage due to rain droplet impact can be found at several locations in blades, however most is found at the leading edge of the blade [60,78,88].…”
Section: Hydrometeors Collisionsmentioning
confidence: 99%
“…Techniques for improving the erosion resistance of the leading edge are also discussed. Later on, Shankar Verma et al [38] showed that a significantly higher erosion damage rate is found for blades exposed to offshore rainfall conditions than for blades under onshore rainfall conditions. Law and Koutsos [39] investigated the energy losses associated with LEE on an operational wind farm, discovering that the average AEP is decreasing by 1.8% due to medium levels of erosion, with the worst affected turbine experiencing losses of 4.9%.…”
Section: Introductionmentioning
confidence: 99%